Astaxanthin Induces Apoptosis in Human Osteosarcoma MG-63 Cells - Wang, Guangyu; Tian, Xu; Liu, Lintao; Dong, Jingming (Folia biologica, 2023)
We explored the mechanism of human osteosarcoma MG-63 cell apoptosis induced by asta-xanthin. The MTT assay was used to detect the effect of astaxanthin on cell viability. Morphological changes associated with apoptosis were observed after DAPI staining. Early and late stages of apoptosis were detected by flow cytometry with annexin V-FITC/PI staining. Activation of caspases-8, -9 and -3 was detected by enzyme activity in vitro. Changes in the mitochondrial membrane potential were detected by MitoCapture staining. Western blot was used to detect the cleavage of PARP, which is a caspase-3 substrate, the release of cytochrome c and Smac into the cytosol, the translocation of pro-apoptotic proteins Bax and Bak, and the expression of mitochondrial pathway-related proteins. The translocation of Bax was also detected by immunofluorescence assay. Astaxanthin significantly inhibited the viability of human osteosarcoma MG-63 cells with an IC50 value of 12.36 μg/ml. The DAPI-stained cells showed characteristic apoptotic morphological changes - cell shrinkage, cell membrane blebbing, nuclear condensation, and apoptotic body formation. Cytochrome c and Smac were released from mitochondria to the cytosol. Pro-apoptotic proteins Bax and Bak were rapidly translocated to mitochondria after six hours of astaxanthin action. Caspases-9 and -3 were activated and PARP was cleaved. The expression of anti-apoptotic proteins Bcl-2, Bcl-xL and XIAP was significantly decreased. Astaxanthin induced human osteosarcoma MG-63 cell apoptosis through the mitochondria-mediated endogenous apoptosis pathway.
Keywords: astaxanthin; Apoptosis Regulatory Proteins; apoptosis; osteosarkom; apoptóza; Apoptosis; MG-63 cells; xanthofyly; Poly(ADP-ribose) Polymerase Inhibitors; cytochromy c; proteiny regulující apoptózu; bcl-2-Associated X Protein; lidé; protein X asociovaný s bcl-2; cytochrome c; Proto-Oncogene Proteins c-bcl-2; PARP inhibitory; mitochondria; Humans; Cytochromes c; protoonkogenní proteiny c-bcl-2; Osteosarcoma; Xanthophylls